Acessibilidade cultural e tecnologia assistiva para pessoas com deficiência intelectual: sistematização de um curso de extensão no Museu da Geodiversidade da Universidade Federal do Rio de Janeiro - Santos, Damiane Daniel Silva Oliveira dos (2023)
The present research presents a qualitative character with the objective of contributing to improve cultural accessibility in museums and Assistive Technology for people with Intellectual Disabilities using Heritage Education and Environmental Education as a theme. The object of the research is the elaboration, execution, evaluation and systematization of the Extension Course “Learning to deal with diversity: Cultural Accessibility and Environmental Education for the public with Intellectual Disability”, offered by the Geodiversity Museum (MGeo) in partnership with the Interdisciplinary Nucleus for Social Development (NIDES). As data collection instruments, the following were used: participant observation, reports, script for systematizing the experience, activity recording chart, semi-open questionnaires, photographs of MGeo accessibility educational activities. The methodological procedure adopted started with a bibliographic survey; followed by the construction and proposition of an extension course, as well as its implementation and analysis. The theoretical framework was based on Environmental Education, Museum Education, Scientific Communication, Cultural Accessibility in Museums, Assistive Technology, Social Technology and Continuing Education of Educators. The main theoretical references were: Paulo Freire, Romeu Sassaki, Viviane Sarraf, Fernanda de Castro, Renato Dagnino, Oscar Hara and relevant legislation. As a main result, the systematization of the extension course experience stands out as a didactic proposal for social transformation.